Bisphenol A-Induced Endocrine Dysfunction and its Associated Metabolic Disorders - Maniradhan, Meenu; Calivarathan, Latchoumycandane (Endocrine, Metabolic & Immune Disorders-Drug Targets, 2023)
Bisphenol A (BPA) is an endocrine-disrupting chemical widely present in many consumer goods that poses a significant threat to our health upon exposure. Humans are exposed to BPA, which directly or indirectly causes endocrine dysfunctions that lead to metabolic disorders like obesity, fatty liver diseases, insulin resistance, polycystic ovarian syndrome, and other endocrine- related imbalances. The duration, quantity, and period of exposure to BPA, especially during the critical stage of development, determine its impact on reproductive and non-reproductive health. Because of its endocrine-disrupting effects, the European Chemical Agency has added BPA to the candidate list of chemicals of very serious concern. Due to its estrogenic properties and structural similarities with thyroid hormones, BPA disrupts the endocrine system at different levels. It interacts with estrogen receptors at the molecular level and acts as an antagonist or agonist via an estrogen receptor-dependent signaling pathway. In particular, BPA binds to G-protein coupled receptors and estrogen receptors, activating signaling pathways that influence cellular apoptosis, proliferation, differentiation, and inflammation. BPA acts as an obesogen that promotes adipogenesis and correlates with increased lipid accumulation and elevated expression of adipogenic markers. As a metabolic and endocrine disruptor, BPA impairs cellular homeostasis by increasing oxidative mediators and decreasing antioxidant enzymes, resulting in mitochondrial dysfunction. Due to its endocrine-disrupting properties, BPA exposure induces endocrine dysfunctions, causing metabolic syndrome. This review article gives recent development and novel insights into the cellular and molecular mechanisms of BPA-induced endocrine dysfunctions and their associated metabolic disorders.
Keywords: metabolic syndrome